Simple Fabrication of Carbon Nanotubes from Ethanol using an Ultrasonic Spray Pyrolysis - Mikrajuddin Abdullah; Ferry Iskandar; Kikuo Okuyama (Institute for Research and Community Services, Institut Teknologi Bandung, 2004)
Carbon nanotubes of diameter (20